VD_FINDINFO Décision / 2013 / 1029 vom 12. November 2013 - VD Tribunal cantonal (2013)
OPPOSITION TARDIVE, ORDONNANCE DE CONDAMNATION, DÉCISION D'IRRECEVABILITÉ | 354 CPP (CH), 356 al. 2 CPP (CH), 393 al. 1 let. b CPP (CH), 85 CPP (CH), 90 CPP (CH)